KOMUNIKASI KEBIJAKAN PEMBANGUNAN DESA DALAM KONTEKS KETERBATASAN GEOGRAFIS DAN DIGITAL: STUDI KASUS DESA BONTO SOMBA DI KABUPATEN MAROS - Muliati Muliati; Ashariana Ashariana; Ibrahim Ibrahim; Asy'hary Asy'hary; Nurkadarwati Nurkadarwati (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
Village development is often hampered by geographic isolation, which disrupts the flow of policy information to remote communities. The focus of this research is to analyze development policy communication practices in Bonto Somba Village, Maros Regency, which faces significant limitations in physical and digital access. The research was conducted using a qualitative, interpretive case study approach, involving village officials and residents as key informants. Key stages included in-depth interviews and participant observation to capture the reality of real-life social interactions in distributing development information. The research findings indicate that policy communication does not operate in a formal, systematic manner, but rather in a hybrid manner, through local actors and strong oral traditions. Village officials play a crucial role as policy translators, filtering information according to residents' needs, while residents rely on intimate, face-to-face social networks. Despite digitalization efforts, its use remains limited to the administrative functions of village government due to inadequate network infrastructure in mountainous areas. Qualitative data confirms that development information is often received fragmentarily and relies solely on local authority figures. The main conclusion of this study is that the effectiveness of policy communication in remote areas is largely determined by the alignment of development messages with the geographic context and local communication culture, not simply the availability of optimal information technology infrastructure for the village community as a whole.